Surface‐enhanced Raman spectroscopy for successful probing of itraconazole within poly(lactic‐co‐glycolic acid) nanoparticles. (21st May 2019) - Ferreira, Queila S.; da Silva, Jaqueline R.; Silva, Renata C.; Py‐Daniel, Karen R.; Azevedo, Ricardo B.; Morais, Paulo C.; da Silva, Sebastião W.
Abstract: The present study reports on successful use of surface‐enhanced Raman spectroscopy to investigate itraconazole (ITZ) molecule loaded within poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles (NPs). SER spectra were recorded by depositing samples onto a nanostructured silver film, which was fabricated via electrolyte deposition of silver NPs onto silver substrate. Transmission electron microscopy, dynamic light scattering, zeta potential, and Fourier transform infrared spectroscopy were employed to support our analyses. While compared with normal Raman spectrum of ITZ powder, changes observed in the SER spectra of the samples comprising ITZ‐loaded PLGA‐NPs (sample ITZ@PLGA‐NPs) and ITZ mixed with PLGA‐NPs (sample ITZ+PLGA‐NPs) provided insights regarding the interaction between the ITZ molecule and both the silver film's surface and the PLGA‐NPs. We found spectral evidences that free ITZ molecule (sample ITZ+PLGA‐NPs) interacts with the silver film's surface via the nitrogen heterocyclic closest to the ITZ's phenyl rings. In this condition, it was verified that the ITZ molecules are more likely oriented parallel to the silver film's surface. Additionally, the ITZ molecule in the ITZ@PLGA‐NPs sample is not adsorbed onto the silver film's surface likely due to steric hindrance provided by the PLGA template. Nevertheless, the SER spectrum of the ITZ@PLGA‐NPs sample shows the signature of the ITZ molecule (likely via the electromagnetic mechanism) and the PLGA template (via the surface adsorption mechanism). Moreover, the SER spectrum recorded from the ITZ@PLGA‐NPs sample indicates weak interaction between the loaded ITZ and the PLGA template. We anticipate that the pioneering approach herein introduced can be successfully used to investigate a wide variety of bioactive molecules encapsulated within polymeric templates, thus providing a very promising, sensitive, and robust analytical tool not yet explored in this regard. Abstract : Loading of itraconazole (ITZ) molecules within poly(lactic‐ co ‐glycolic acid) (PLGA) nanoparticles was studied by surface‐enhanced Raman spectroscopy. The data showed that despite effective encapsulation of the drug, a weak interaction between the ITZ and the PLGA template takes place. Our findings suggest that while interacting with the silver film's surface, the ITZ's phenyl and the triazole planes are, respectively, parallelly and perpendicularly oriented.